PERANCANGAN SISTEM INFORMASI PENGELOLAAN PRAKTEK KERJA LAPANGAN DENGAN METODE PROTOTYPE (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Nowadays, the development of IT provides many benefits for all levels of society as a solution to the problems of a job. The Faculty of Tourism of Udayana University is one of the higher education institutions that also utilizes existing IT. Data management in each study program, section or work unit used an online information system. However, in the midst of a system that is already running well, there is still a system that is carried out manually and it is very necessary to be developed in order to provide more optimal services to students, namely the Student Field Work Practice (PKL) management system. In its current management, it is still using the Ms. Word and Excel. The data is stored in several separate files so that it can result in repeated data input and takes a long time to complete the administration of student street vendors, which is only handled by one employee. Based on these problems, the authors consider it necessary to design and build a web-based Job Training Management Information System. In designing this system using the waterfall development method. The results of this study are expected to produce a design system to help settle the administration of street vendors better, so as to produce more complete, accurate and precise reports for students, lecturers and faculty leaders. Keywords: Information Systems, Data Flow Diagram, PKL, Prototyping Model, Faculty of Tourism